O pojmowaniu praworządności socjalistycznej w Polsce Ludowej - Lityński, Adam (Czasopismo Prawno-Historyczne, 2007)
The very essence of understanding the notion and meaning of law and order is the concept of law and the role assigned to it in a given state. Following the views of Marx and Engels, Vladimir IIich Ulyanov-Lenin saw law as an instrument of class domination. Such an interpretation of law had its logical consequence in the recognition that the state authority stood above the law, and that dictatorship was ‘nothing else but power limited by no constraints and bound by no laws’ (Lenin). A classical approach to law and order, however, did not apply in a situation when the power remained in the Bolsheviks’ hands. In line with that Soviet theory, the Polish People’ Republic used first, the notion of people’s law and order, which was later replaced by socialist law and order. The socialist law constituted a completely different ideological concept, related to the doctrine of the communist state and law. According to that concept, the very idea of the socialist law and order derived from other values contained in law. This approach, however, or a socialist system of law and order, did not adequately respond to the needs of Europe in the 20th century.